Abdominal swelling in two teenage girls: two case reports of massive ovarian tumours in puberty. (15th May 2012) - Willems, Rick P P; Slangen, Brigitte; Busari, Jamiu O
Abstract : The following report describes two 15-year-old girls with a giant abdominal swelling. Signs and symptoms differed between those two girls, as serum tumour markers showed different elevation patterns. Additional investigations including a CT scan and a MRI scan were performed and revealed masses originating from the ovary. Histopathological evaluation after cystectomy showed a mature teratoma and a mucinous cystadenoma.